2007
DOI: 10.1007/s12010-007-8076-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gene Orientation and Use of Multiple Promoters on the Expression of XYL1 and XYL2 in Saccharomyces cerevisiae

Abstract: Orientation of adjacent genes has been reported to affect their expression in eukaryotic systems, and metabolic engineering also often makes repeated use of a few promoters to obtain high expression. To improve transcriptional control in heterologous expression, we examined how these factors affect gene expression and enzymatic activity in Saccharomyces cerevisiae. We assembled D-xylose reductase (XYL1) and D-xylitol dehydrogenase (XYL2) in four ways. Each pair of genes was placed in two different tandem (1-->… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…These effects were abolished when the two transcriptional processes were not simultaneous, confirming the strong TI in the case of simultaneous transcription. Contrarily to previous studies (Bae et al, 2008; Lee et al, 2014), our results provide a clear indication that relative positioning of three contiguous transcription units and their orientations probably induce TI on a multicopy plasmid. Large TI effects demonstrated in our design may be related to terminators efficiency, and are probably accentuated by the absence of extra-space between our three transcription units.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These effects were abolished when the two transcriptional processes were not simultaneous, confirming the strong TI in the case of simultaneous transcription. Contrarily to previous studies (Bae et al, 2008; Lee et al, 2014), our results provide a clear indication that relative positioning of three contiguous transcription units and their orientations probably induce TI on a multicopy plasmid. Large TI effects demonstrated in our design may be related to terminators efficiency, and are probably accentuated by the absence of extra-space between our three transcription units.…”
Section: Discussionsupporting
confidence: 86%
“…TI is defined as the suppressive influence of one transcriptional process, directly and in cis, on a second transcriptional process (Shearwin et al, 2005). This phenomenon was well-studied with native S. cerevisiae genes (Prescott and Proudfoot, 2002; Wang et al, 2014) but only two studies addressed the case of TI in heterologous expression, demonstrating transcription inhibition effects only in the case of divergent genes (Bae et al, 2008; Lee et al, 2014). It is known that the genome of S. cerevisiae is highly compact (an ORF every 2 kb in average) and less than 6% of the convergent adjacent genes show a pattern of co-expression.…”
Section: Discussionmentioning
confidence: 99%
“…Coexpression can be explained by bidirectional transcription attributable to various factors, including common cis -regulatory elements (in MAL6T-MAL6S ) (Bell et al 1995) or chromatin organization (in UGA3-GLT1 ) (Ishida et al 2006). In contrast, some studies reported no dependence on gene orientation (Bae et al 2008) and others reported anticorrelated gene expression between divergent genes (Lin et al 2007). Multiple factors may account for the differences in how divergent promoters behave, including the structure and properties of promoters ( i.e.…”
Section: Discussionmentioning
confidence: 96%